2007
DOI: 10.1016/j.pecs.2006.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of fluidized bed combustion—An overview of trends, performance and cost

Abstract: The goal of this article is to chart and analyse the development and economical performance of fluidized bed combustion (FBC) and its derivates circulating fluidized bed (CFB) and bubbling fluidized bed (BFB). A descriptive overview is given of the technology and the market penetration is discussed. To make further analysis possible a database is constructed. This database comprises technological and economical data on 491 FBC projects. Analysis of these projects shows that the technology variants (CFB and BFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(137 citation statements)
references
References 21 publications
2
131
0
4
Order By: Relevance
“…Manufacturers can use this information to improve their respective products [24][25][26]. Furthermore, companies, users, project developers and other stakeholders-such as research institutes and policymakers-can learn from one another through the formal and informal exchange of information [27][28][29].…”
Section: Deployment-induced Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Manufacturers can use this information to improve their respective products [24][25][26]. Furthermore, companies, users, project developers and other stakeholders-such as research institutes and policymakers-can learn from one another through the formal and informal exchange of information [27][28][29].…”
Section: Deployment-induced Learningmentioning
confidence: 99%
“…Economies of scale at manufacturing level do not appear to have played a significant role in influencing the costs of fossil fuel plants in the past, even though some literature sources suggest that standardisation and the ensuing potential for mass production and economies of scale may have played a role in reducing the costs over time of fluidized bed combustion boilers [25,28]. The limited role played by economies of manufacturing scale in large-scale fossil fuel power plants can be explained by the much lower number of identical (or similar) plants required by these technologies, compared to small-scale renewable energy technologies, to achieve a certain level of electricity generation.…”
Section: Economies Of Manufacturing Scale (Mass Production)mentioning
confidence: 99%
See 1 more Smart Citation
“…Fluidized bed combustion represents a straightforward evolution of the circulating fluidised bed combustion, which has gained great attention from the Seventies [16]. Fluidization means that the solid coal particles are supported and mixed with air which is injected into the system.…”
Section: Pressurized Fluidized Bed (Pfbc)mentioning
confidence: 99%
“…It is usually concluded that a replacement of OPC higher than 5-10 % has an adverse effect on the compressive and tensile strengths. 4 FBC technology has many advantages in comparison with pulverized coal combustion, 5 but the ashes from FBC are very porous and they contain high amounts of very reactive free lime and anhydrite, which lead, on the one hand, to their self-cementing properties, but, on the other hand, to the problems with the workability and volume stability due to the formation of expansive-hydration products.…”
Section: Introductionmentioning
confidence: 99%